The pecking order of cross-border investment - Christian Daude; Marcel Fratzscher (European Central Bank (ECB), 2006)
Is there a pecking order of cross-border investment in that countries become financially integrated primarily through some types of investment rather than others? Using a novel database of bilateral capital stocks for all types of investment – FDI, portfolio equity securities, debt securities as well as loans – for a broad set of 77 countries, we show that such a pecking order indeed exists. Motivated by the theoretical work on the capital structure of firms, the paper focuses on two key determinants of this pecking order: information frictions and the quality of host country institutions. Overall, we find that in particular FDI, and to some extent also loans, are substantially more sensitive to information frictions than investment in portfolio equity and debt securities. We also show that the share as well as the size of FDI that a country receive are largely insensitive to institutional factors in host countries, while portfolio investment is by far the most sensitive to the quality of institutions. This provides new evidence in favor of some hypotheses but contradicts others put forward in the theoretical literature on trade in financial assets.
Keywords: F34; G11; F21; 330; Capital flows; foreign investment; gravity; home bias; information frictions; institutions; pecking order; Auslandsinvestition; Portfolio-Investition; Anleihe; Kapitalmobilität; Vollkommene Information; Institutionelle Infrastruktur; Welt